Requiem or revival? : the promise of North American integration - Studer-Noguez, Isabel, 1963-; Wise, Carol (Brookings Institution Press, 2007)
"Within NAFTA, explores interactions between regionalism and multilateralism, the impact of the "new trade" agenda, and unresolved problems--migration, security, and energy. Discusses NAFTA's relationship to the Free Trade Agreement of the Americas negotiations and the Doha Development Round and various ways in which NAFTA could be revamped or improved"--Provided by publisher